2014
DOI: 10.1097/mpg.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acoustic Radiation Force Impulse/Serum Noninvasive Markers for Fibrosis Prediction in Liver Transplant

Abstract: ARFI may serve as a potential method for assessing significant fibrosis in pediatric patients with liver transplant, particularly in combination with AST/ALT ratio index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
3
25
4
2
Order By: Relevance
“…There was no overlap in mean shear wave speed measurements between the biliary atresia and non-biliary atresia groups. Our observed shear wave speeds are in general agreement with previously reported values for individuals with and without liver fibrosis [8,9,[26][27][28]. Given the novelty of VTIQ imaging, no previously reported values are available for which to compare our VTIQ results.…”
Section: Discussionsupporting
confidence: 93%
“…There was no overlap in mean shear wave speed measurements between the biliary atresia and non-biliary atresia groups. Our observed shear wave speeds are in general agreement with previously reported values for individuals with and without liver fibrosis [8,9,[26][27][28]. Given the novelty of VTIQ imaging, no previously reported values are available for which to compare our VTIQ results.…”
Section: Discussionsupporting
confidence: 93%
“…Through multivariate logistic regression analysis, the only independent predictor of significant fibrosis was SWV. SWV assessment may serve as a potential method for assessing significant fibrosis in pediatric patients with liver transplants, particularly in combination with AST/ALT ratio [64].…”
Section: Liver Fibrosismentioning
confidence: 99%
“…However, Wildner and associates 4 reported that the areas under the receiver operating characteristic curves for patients with advanced fibrosis (F3) and cirrhosis (F4) (by Batts-Ludwig scoring) were 92.9% and 80% and had discretely higher cutoff values (≥ F1, 1.48 m/s). Pinto and associates 22 indicated a statistically significant difference in shear-wave velocities between the F0-F1 and F2-F4 groups (by Batts-Ludwig scoring), concluding that ARFI might serve as a potential method for assessing significant fibrosis in pediatric patients after liver transplant. Tomita and associates 23 reported that the ARFI measurements were significantly higher for patients with F1 and F2 portal fibrosis versus patients with F0 portal fibrosis (by METAVIR scoring).…”
Section: Discussionmentioning
confidence: 99%
“…5,18,[21][22][23] Liao and associates 21 reported a sensitivity ratio of 95.5% using a shear-wave velocity cutoff value of 1.058 m/s in the evaluation of posttransplant graft dysfunction in early fibrosis stages (≤ F1, by METAVIR scoring); which constituted a larger proportion of the study group (94.5%). The group indicated that there was a significant difference in F0 compared with F1.…”
Section: Discussionmentioning
confidence: 99%